2022
DOI: 10.3389/fimmu.2022.867261
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in Liver Failure Syndromes: A Focus on Eicosanoids, Specialized Pro-Resolving Lipid Mediators and Lysophospholipids

Abstract: Lipids are organic compounds insoluble in water with a variety of metabolic and non-metabolic functions. They not only represent an efficient energy substrate but can also act as key inflammatory and anti-inflammatory molecules as part of a network of soluble mediators at the interface of metabolism and the immune system. The role of endogenous bioactive lipid mediators has been demonstrated in several inflammatory diseases (rheumatoid arthritis, inflammatory bowel disease, atherosclerosis, cancer). The liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 286 publications
(326 reference statements)
0
11
0
Order By: Relevance
“…Lastly, as cell membrane PE can be a source of substrates for eicosanoid biosynthesis 32 , and as hepatocyte-derived eicosanoids are implicated in NASH pathogenesis 33 , we measured a panel of eicosanoids in the WD-fed mouse livers. None of the 19 detected eicosanoid species had different levels in Tlcd1/2 DKO livers compared to controls (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, as cell membrane PE can be a source of substrates for eicosanoid biosynthesis 32 , and as hepatocyte-derived eicosanoids are implicated in NASH pathogenesis 33 , we measured a panel of eicosanoids in the WD-fed mouse livers. None of the 19 detected eicosanoid species had different levels in Tlcd1/2 DKO livers compared to controls (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that adrenic acid, an arachidonic acid‐derived metabolite, exerts a powerful anti‐inflammatory effect by inhibiting LTB4 production in neutrophils (Brouwers et al, 2020). Similarly, lipoxin A4 and lipoxin B4, derivatives of AA, have been reported to exert anti‐inflammatory effects by reducing neutrophil recruitment on inflammation sites as well as enhancing efferocytosis (Artru et al, 2022). Unlike eicosanoid pro‐inflammatory mediators, studies have found that ω ‐3 PUFAs such as docosahexaenoic acid and eicosapentaenoic acid oxygenated metabolites resolvin D1 and resolvin E1 are synthesized during the resolution phase of inflammatory exudates and have potent anti‐inflammatory and immunomodulatory effects (Serhan, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that adrenic acid, an arachidonic acid-derived metabolite, exerts a powerful anti-inflammatory effect by inhibiting LTB4 production in neutrophils (Brouwers et al, 2020). Similarly, lipoxin A4 and lipoxin B4, derivatives of AA, have been reported to exert anti-inflammatory effects by reducing neutrophil recruitment on inflammation sites as well as enhancing efferocytosis (Artru et al, 2022). Unlike eicosanoid pro- (Burstein et al, 2011).…”
Section: Fatty Acid Metabolismmentioning
confidence: 99%
“…One of the crucial steps of this pathway is indeed performed by LPCAT3 53 , selectively activated by Interferongamma, which incorporates polyunsaturated fatty acids (PUFA)-CoA into phospholipids, using J o u r n a l P r e -p r o o f phosphatidylcholines and phosphatidylethanolamine as substrates. Indeed, the links between lipid metabolism and immune system are multiple and many lipid mediators have been studied in ferroptosis including specialized pro-resolving mediators that would be an interesting research focus in acute liver failure 54 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%